A personalized 3D-printed plate for tibiotalocalcaneal arthrodesis: Design, fabrication, biomechanical evaluation and postoperative assessment. (June 2021) - Yao, Yan; Mo, Zhongjun; Wu, Gang; Guo, Junchao; Li, Jian; Wang, Lizhen; Fan, Yubo
Abstract: Personalized plates (P-Plates) could provide improved clinical outcomes in joint fusion by enabling perfect geometric matching between irregular bone and implants. However, there is no unified application framework for P-Plates for joint fusion. The objective of this study was to develop such a framework for P-Plates for tibiotalocalcaneal arthrodesis. A patient-specific bone model was constructed based on CT images, and the P-Plate was preliminarily designed to match the bones. Finite element method was used to optimize the stress distribution and to evaluate the biomechanical performance of the P-Plate by comparing it with a traditional plate (T-Plate). Then, the P-Plate was manufactured via electron beam melting and implanted into the foot of a patient. Increasing the size of the preliminary designed plate alleviated the stress concentration and reduced the risk of failure. The maximum stresses of the plate and screw (214.3 MPa, 99.05 MPa) and the maximum tensile force of the screw in the P-Plate (181.4 N) fixation system were lower than those in the T-Plate (217.4 MPa, 255.4 MPa, and 230.1 N, respectively). The P-Plate was well-matched to the bone, and no complications occurred. The P-Plate achieved American Orthopaedic Foot & Ankle Society and Short-Form-36 scores of 64 and 75, respectively, 36 months post operation, which suggests that it could improve clinical outcomes. The design and fabrication methods, as well as mechanical and postoperative performance evaluation methods, for the P-Plate were systematically developed and provide a reference for constructing a unified application framework for P-Plate use in tibiotalocalcaneal arthrodesis. Graphical abstract: Image 1 Highlights: An application framework of P-Plates for joint fusion was proposed. The P-Plate exhibited superior mechanical performance under physiological loading. The P-Plate was well-matched to the bone and no complications had developed. Postoperative evaluations provided that the P-Plate can improve clinical outcomes.